Three kinds of suffering and their relative moral significance - Kious, Brent M. (Bioethics, 2022)
Suffering is widely assumed to have particular moral significance, and is of special relevance in medicine. There are, however, many theories about the nature of suffering that seem mutually incompatible. I suggest that there are three overall kinds of view about what suffering is: value-based theories, including the theory famously expounded by Eric Cassell, which as a group suggest that suffering is something like a state of distress related to threats to things that a person cares about; feeling-based theories, which equate suffering with aversive feelings or sensations like pain; and objective theories, which suggest that suffering is the absence of objective flourishing. Rather than argue that one or another of these kinds of theory most accurately captures the nature of suffering, I allow that the term is ambiguous and thus that it may have at least three different kinds. I further argue, however, that when we think about suffering as potentially justifying end-of-life interventions, especially for cognitively typical adults, we are interested mainly in value-based suffering. This is because the moral significance of value-based suffering for persons with decision-making capacity generally outweighs that of the other types; those other types of suffering achieve overriding moral significance only if they also constitute, or contribute to, value-based suffering.